Amphiphilic diethylaminoethyl chitosan of high molecular weight as an edible film - da Mata Cunha, Otávio [UNESP] (2020)
Edible films and coatings can enhance the quality of food products, protecting them from biological deterioration, especially against fungal diseases and pathogenic microorganisms. In this study, films from chitosan, diethylaminoethyl-chitosan (DEAE-CH) and its hydrophobicized derivative DEAE-CH-DD were prepared by casting and their physicochemical and antimicrobial properties evaluated. The grafting with DEAE and dodecyl groups resulted in films with an elasticity modulus up to five times higher than commercial chitosan and increased water vapor permeability. Field emission gun - scanning electron microscopy and atomic force microscopy techniques showed films with smooth surfaces and the contact angle measurements revealed a correlation between the grafted group and hydrophilic/hydrophobic nature of the surface of the film. The amphiphilic derivatives exhibited better antimicrobial activity than unmodified chitosan against Penecillium expansum, Alternaria alternata and Alternaria solani. The amphiphilics DEAE-CH and DEAE-CH-DD showed no toxicity and delayed rotting and loss of water in strawberries and bananas, suggesting that this kind of film has great potential for increasing the shelf-life of different fruits.